Gender and action films 2000 and beyond : transformations - Gerrard, Steven; Middlemost, Renée (Emerald studies in popular culture and gender., 2022)
Lying at the heart of the modern Action Cinema Canon is the concept of transformation. As the action genre evolves and shifts into the new millennia, innovative additions blend with nostalgic returns - the move away from a male-dominated space to feature even more prominent female roles co-exists alongside a revival of Arnold Schwarzenegger and Linda Hamilton, and series such as Rocky and Rambo return to the screens. Gender and Action Films 2000 and Beyond: Transformations captures and explores the nuanced and complex nature of change within Action Cinema. Dealing with the notion of aging, the chapter authors consider how action heroes confront and cope with getting older. Expanding the foundation of research on geriaction stars, the advantages of mature masculinity contrasts with themes of masculine fragility. Viewing the action genre through a feminist lens, this edited collection traces the evolution of the representation of women, suggesting how such roles may develop in the future. Finally, a consideration of the post-millennial boom of movie backdrops in turmoil analyses how such pieces question and contribute to debates on global political and social issues. Gender and Action Films 2000 and Beyond: Transformations looks at Action Cinema from the old to the new, offering an exciting interrogation of the portrayal of gender in the new millennia. A necessity for academics, students and lovers of film and media and those interested in gender studies.